On the Need of Angle Diversity Receiver for Downlink NOMA-Based Visible Light Communication Systems - Al-Sakkaf, Ahmed Gaafar Ahmed; Morales-Cespedes, Maximo (IEEE open journal of the Communications Society, 2025)
Non-orthogonal multiple access (NOMA) has been proposed as a promising candidate technology for the next generation multiple access (NGMA). Applied to visible light communication (VLC), NOMA is subject to the small and confined coverage footprint provided by each optical access point (AP), which leads to small channel differences among users within the coverage footprint of the same optical AP as well as to intercell interference from neighboring APs. This condition may result in a poor performance of NOMA. In this work, we analyze the impact of angle diversity receivers (ADRs) on the performance of NOMA in VLC. The concept of tangential power allocation (TPA) is proposed to obtain a trade-off between achievable sum-rate and fairness. Specifically, two methodologies are proposed to calculate the TPA coefficients for ADRs assuming both approaches to manage the combination of photodiodes; select best combining (SBC) and maximum ratio combining (MRC). Simulation results show that the concept of ADR considerably increases the number of users that can be served by applying NOMA. Moreover, the SBC approach provides similar rate to MRC, which motivates to relax the complexity of the receivers. It is also shown that the proposed TPA achieves a greater performance in terms of sum-rate and fairness than baseline power allocation schemes.